Reconstructing the Concept of Nafkah in Islamic Legal Thought: Gender Reciprocity and Female Breadwinners In the Javanese Priyayi Society Culture, Java - Elfa Murdiana; Evi Muafiah; Lutfiana Dwi Mayasari; Dede Nurohman; Nandang Kosim (Justicia Islamica, 2025)
This article interrogated the phenomenon of female breadwinners within Javanese society, with a particular focus on priyayi women from both the royal court and the contemporary elite. It explores how evolving gender roles contest classical Islamic jurisprudential frameworks regarding financial responsibility (nafkah). The central aim is to reconceptualise nafkah in Islamic legal discourse, critically examine the impact of Javanese cultural paradigms on women’s social positioning, and advocate for a more contextually nuanced and inclusive Islamic legal framework that accurately reflects the lived experiences of Muslim women in Java. Employing a qualitative methodology that integrates textual analysis, in-depth field interviews, and the theoretical lenses of individual resilience, maqāṣid al-shariah, and mubādalah (reciprocity), the research elucidates the extraordinary social and spiritual resilience displayed by priyayi women as they navigate patriarchal stigma and the complexities of dual economic responsibilities. Cultural constructs such as nrimo (acceptance) and laku spiritual (spiritual practice) are not merely passive acquiescence but are reframed as adaptive strategies consonant with the values of maṣlaḥah (public welfare) and iḥsān (moral excellence). Drawing upon these insights, the study advocates for a contextual reconstruction of gender roles in Islamic law, anchored in three foundational principles: reciprocity (mubādalah), public benefit (maṣlaḥah), and cultural contextuality. Ultimately, the article argues that Javanese female breadwinners should not be seen as anomalies within Islamic tradition, but rather as living manifestations of justice, equality, and humanistic values, situated within an evolving, culturally embedded understanding of Islam.